Planktonic foraminifera assemblages and sea surface temperature reconstruction of IODP Site 383-U1539 - Maria Júlia de Castro; Igor Martins Venancio; Thiago Santos; Douglas Villela de Oliveira Lessa; João M Ballalai; Ana Luiza Albuquerque (PANGAEA, 2025)
This dataset comprises planktonic foraminifera assemblages and sea surface temperature (SST) reconstructions generated using the Modern Analogue Technique (MAT). The record spans 0.5 to 1.3 Ma, covering intervals before, during, and after the Middle Pleistocene Transition (MPT). It includes the sample code, depth in meters CSF-A (core depth below seafloor, method A), interpolated age in million years (Ma), sea surface temperature (°C) with associated weighted standard deviation, as well as the relative abundances (%) of planktonic foraminifera species. Sediment was recovered by drilling during IODP Expedition 383 at Site U1539, located in the South Pacific sector of the Southern Ocean. Samples were washed through a 63 μm mesh size sieve and subsequently dried at approximately 50°C for 24 hours. Once dried, samples were sieved through a 250 μm mesh. Species-level identification was performed using a stereomicroscope. These assemblage data were used to reconstruct SSTs with the MAT, implemented in C2 Software (version 1.8.0), using the Squared Chord Distance dissimilarity coefficient and leave-one-out cross-validation. The resulting SST estimates were applied as a proxy to investigate the latitudinal migration of oceanic fronts-particularly the Polar Front-during the MPT, to assess the mechanisms driving these shifts and their impact on the central South Pacific. The use of foraminiferal assemblages as a proxy for palaeoceanographic changes follows Kucera (2007; https://doi.org/10.1016/S1572-5480(07)01011-1).